Identification of Hub Genes Associated With Development of Head and Neck Squamous Cell Carcinoma by Integrated Bioinformatics Analysis - Li, Chia Ying; Cai, Jia-Hua; Tsai, Jeffrey J. P.; Wang, Charles C. N. (Frontiers in Oncology, 2020)
Improved insight into molecular mechanism of head and neck squamous cell carcinoma (HNSCC) is required to predict prognosis and develop a new therapeutic strategy for targeted genes. The aim of this study is to identify significant genes associated with HNSCC and further analyze its prognostic significance. In our study, the cancer genome atlas (TCGA) HNSCC database and the gene expression profiles of GSE6631 from Gene Expression Omnibus (GEO) were used to explore the differential co-expression genes in HNSCC compared with normal tissues. A total of 29 differential co-expression genes were screened out by Weighted Gene Co-expression Network Analysis (WGCNA) and differential gene expression analysis methods. As suggested in functional annotation analysis using R clusterProfiler package, these genes were mainly enriched in epidermis development and differentiation (biological process); apical plasma membrane and cell-cell junction (cellular component); and enzyme inhibitor activity (molecular function). Furthermore, in a protein-protein interaction (PPI) network containing 21 nodes and 25 edges, the ten hub genes (S100A8, S100A9, IL1RN, CSTA, ANXA1, KRT4, TGM3, SCEL, PPL, and PSCA) were identified using the CytoHubba plugin of Cytoscape. The expression of the ten hub genes was all downregulated in HNSCC tissues compared with the normal tissues. Based on survival analysis, the lower expression of CSTA was associated with worse overall survival (OS) in patient with HNSCC. Finally, the protein level of CSTA, which was validated by Human Protein Atlas (HPA) database, was down-regulated consistently with mRNA level in head and neck cancer samples. In summary, our study demonstrated that survival-related gene is highly correlated with head and neck cancer development. Thus, CSTA may play important roles in the progression of head and neck cancer and serve as potential biomarkers for future diagnosis and treatment.